2009
DOI: 10.1080/01426390903177276
|View full text |Cite
|
Sign up to set email alerts
|

Do Highly Modified Landscapes Favour Generalists at the Expense of Specialists? An Example using Woodland Birds

Abstract: when living in such highly modified secondary habitats (small woods, parks, farmland). Within-habitat heterogeneity (using the example of Monks Wood NNR) is generally associated with greater species diversity, but to benefit from heterogeneity at a landscape-scale may require both high mobility and the ability to thrive in small habitat patches. Modern landscapes, dominated by small, modified and scattered habitat patches, may fail to provide specialists, especially sedentary ones, with access to sufficient qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 53 publications
0
12
1
Order By: Relevance
“…Studies of energetics in the sites presently being considered have shown that breeding birds work much harder to produce fewer offspring in urban habitats as compared to woodland [48,49]. The present study found all of the birds struggling to raise young in 2012, but the variable performance of birds in riparian and urban habitats was not very different from a typical year, whereas the early laying birds breeding at BW performed particularly poorly.…”
Section: Discussioncontrasting
confidence: 45%
“…Studies of energetics in the sites presently being considered have shown that breeding birds work much harder to produce fewer offspring in urban habitats as compared to woodland [48,49]. The present study found all of the birds struggling to raise young in 2012, but the variable performance of birds in riparian and urban habitats was not very different from a typical year, whereas the early laying birds breeding at BW performed particularly poorly.…”
Section: Discussioncontrasting
confidence: 45%
“…Landscape modification by human activity tends to reduce semi-natural habitat to small, scattered patches (Sala et al 2000, Hinsley et al 2009). Pressures on land use produce a fine-grained landscape within which large tracts of particular habitat types are usually rare.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence that widowed adults will leave territories in order to seek breeding opportunities suggests that loss of one bird in a pair may lead to both birds disappearing from a wood, which will accelerate extinction within small fragments as isolation increases. Marsh Tits in highly modified landscapes such as England may, therefore, be particularly vulnerable to local extinctions as a result of the interaction between behavioural ecology and increasing habitat fragmentation (Hinsley et al 2009). …”
Section: Discussionmentioning
confidence: 99%